Implementasi Augmented Reality Pada Aplikasi HOPE Berbasis Android - Ihzany Vilia Devi; Suroso Suroso; Nasron Nasron (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
In studying telecommunications, students are required to master telecommunications equipment that is often used in laboratories. The high cost of telecommunications equipment causes students to take turns in observing and studying telecommunications equipment. If students are not careful in using telecommunications equipment owned by the laboratory, it is likely that the equipment will be damaged quickly, causing the learning process to be disrupted. Then we need an interactive application that can provide visual and auditory learning based on Android that can be accessed anytime and anywhere. So in this study, a HOPE application which means